Zwitterionic iodonium salts as tectons for design of halogen bonded organic frameworks (XOFs) - Soldatova N. S. Nataliya Sergeevna (Non-covalent interactions in crystalo-chemical design and supramolecular chemistry, 2021)
Заглавие с титульного экрана